Un/Detectability in Times of “Equality”: HIV, Queer Health, and Homonormativity - Jan Huebenthal (European Journal of American Studies)
As medical advances have made HIV survival possible, narratives of “undetectable” viral loads often fail to account for the multiple layers of racial and political privilege that animate and sustain them. For example, African American men who have sex with men are eight times more likely than whites to be diagnosed with HIV, and one in two gay black men will likely be diagnosed with HIV in his lifetime—and African Americans face low rates of access to and retention in HIV care. Drawing on dis/ability and queer theory, this article critiques the ways in which “undetectability” discourses proffer AIDS erasure, whiteness, and ideologies of able-bodiedness as central to homonormative LGBT identity politics. Based in normative modes of disciplinary, hygienic sexuality, narratives and realities of carefully managed HIV infection emerge in support of LGBT desires for state recognition. In this process, an emphasis on personal, rather than systemic, responsibility has tied HIV care and survival to grids of racial, political, and ultimately individual privilege. Weighing the ethical residues of LGBT rights “victories,” this essay argues that access to the private spheres of marriage, child-rearing, and inheritance has come at the expense of the health of vulnerable populations and breathed new life into specters of homophobia and AIDS stigma.